Implementasi dan Urgensi Integrasi Prinsip Green Chemistry dalam Praktikum IPA di Sekolah: A Literatur Review - Perta, Hendro; Helti Riana; Thoriq; Dita Arisona (Universitas Garut, 2025)
This study aims to examine the application of Green Chemistry principles in science practicum at schools as an effort to achieve safe, environmentally friendly, and sustainable learning. The method employed was a literature review with a descriptive qualitative approach, analyzing scientific articles published in national and international journals. The findings indicate that Green Chemistry can be implemented through the substitution of hazardous chemicals with safer alternatives, the use of micro-scale experiments to minimize waste, and the development of environmentally friendly practicum modules. The benefits include improved students’ science process skills, reduced laboratory accidents, and the development of environmental awareness. Nevertheless, challenges remain, such as limited laboratory facilities, insufficient teacher competence, and the absence of explicit policy support. This review concludes that Green Chemistry plays a crucial role in strengthening contextual, safe, and sustainable science learning that aligns with the demands of 21st-century education Keywords: Green Chemistry, science practicum